2019
DOI: 10.1080/09243453.2019.1642215
|View full text |Cite
|
Sign up to set email alerts
|

The informed choice: mathematics textbook assessment in light of educational freedom, effectiveness, and improvement in primary education

Abstract: In many educational systems, textbooks are a leading factor for daily instructional practices, and consequently may affect educational outcomes.Whereas in many countries, textbook assessment is a common practice in light of evaluating and improving educational effectiveness, in other countries these practices are absent, mainly under the realm of educational freedom. In this study, we attempt to highlight the potential contribution of textbook assessment to educational freedom, effectiveness and improvement, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…Accordingly, we cannot reject the null hypotheses that the textbooks do not affect children's learning progress in reading comprehension and engagement in reading. These results are somewhat surprising, given that former research on the effects of textbooks generally found significant effects for academic performance (Goffin et al, 2016;Bellens et al, 2019(e.g., Törnroos, 2005Van Steenbrugge et al, 2013;Hadar, 2017;van den Ham and Heinze, 2018). Furthermore, there are also several theoretical reasons to expect that textbooks matter for student's academic performance (Schmidt et al, 1997;Valverde et al, 2002;Törnroos, 2005) in reading comprehension and engagement.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Accordingly, we cannot reject the null hypotheses that the textbooks do not affect children's learning progress in reading comprehension and engagement in reading. These results are somewhat surprising, given that former research on the effects of textbooks generally found significant effects for academic performance (Goffin et al, 2016;Bellens et al, 2019(e.g., Törnroos, 2005Van Steenbrugge et al, 2013;Hadar, 2017;van den Ham and Heinze, 2018). Furthermore, there are also several theoretical reasons to expect that textbooks matter for student's academic performance (Schmidt et al, 1997;Valverde et al, 2002;Törnroos, 2005) in reading comprehension and engagement.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, even after controlling for student characteristics, differences between textbooks remained. Notably, both Goffin et al (2016) and Bellens et al (2019) found similar patterns for which specific textbooks were more effective for mathematics than others.…”
Section: Effects Of Textbooksmentioning
confidence: 75%
See 1 more Smart Citation
“…Developing high-quality textbooks is cardinal for ensuring students' mathematical learning opportunities and improving their outcomes (Bellens et al, 2020;Hadar, 2017). Existing literature has offered guidance on how to design fraction addition and subtraction problems with regard to horizontal and vertical dimensions (e.g., Son, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the students who learned mathematics with a low level of cognitive demands tasks tended to develop low-order thinking skills, such as recalling and computation (Mullis et al, 2012;Tan et al, 2018). As different learning opportunities lead to different mathematical outcomes (Bellens et al, 2020;Hadar, 2017;van den Ham & Heinze, 2018), developing a high-quality mathematics textbook is a critical issue for educators.…”
mentioning
confidence: 99%